First Aid for Wounds: Health Education for Elementary School Students - Rasyid, T. Abdur; Kartika, Defi Eka; Indra, Rani Lisa; Saputra, Bayu; Sandra, Sandra; Wulandari, Dwi (Karya Kesehatan Siwalima, 2025)
Minor injuries such as abrasions and lacerations are common among elementary school students, particularly due to play activities, while limited knowledge and skills in first aid may increase the risk of infection and wound-related complications. This community service program aimed to enhance students’ understanding and practical skills in managing minor injuries through structured health education on first aid for wounds. The activity was conducted at SDN 21 Pekanbaru with 18 students as participants. The program included interactive lectures, practical demonstrations of wound care, and the use of audiovisual media as learning tools. Data were collected using pre-test and post-test questionnaires to measure knowledge improvement in minor wound first aid, complemented by direct observation to evaluate first aid skills. Results showed a significant knowledge gain, with mean scores increasing from 76.67 before the intervention to 100 after the session. Similarly, observational scores of first aid skills rose markedly from 32.78 to 100, reflecting substantial competency gains following the educational program. These findings confirm that combining lectures, demonstrations, and audiovisual support is an effective strategy to promote both cognitive and psychomotor domains of learning in elementary students. The program not only improved students’ ability to respond to minor injuries and fostered health literacy applicable in daily life, but also highlights the need for future school-based initiatives in collaboration with Public Health Centers (Puskesmas) to provide first aid training for students and teachers, thereby enhancing preparedness, strengthening competencies, and promoting a sustainable culture of safety and health in schools